Decreased Serum and Tissue Levels of Isthmin-1 in Patients With Idiopathic Granulomatous Mastitis: A Case-Control Study - Karatas, Ahmet; Oz, Burak; Akkoc, Ramazan Fazil; Ozercan, Ibrahim Hanifi; Koca, Suleyman Serdar (Wiley, 2025)
Background Idiopathic granulomatous mastitis (IGM) is a chronic inflammatory breast disorder with unclear etiology. Isthmin-1 (ISM1), a secreted protein with anti-inflammatory properties, has not been previously studied in IGM. Objective This study aimed to compare serum and tissue ISM1 levels between IGM patients and healthy controls, and to assess its diagnostic potential. Methods This case-control study included 30 women with histopathologically confirmed IGM and 30 age-matched controls undergoing breast reduction surgery. Serum and tissue ISM1 levels were measured using ELISA. Receiver operating characteristic (ROC) analysis assessed the diagnostic performance of serum ISM1. Results ISM1 concentrations were significantly lower in IGM patients compared to controls in both serum (541.42 +/- 191.01 vs. 1139.19 +/- 698.43 pg/mL; p = 0.019) and tissue (511.07 +/- 188.16 vs. 778.24 +/- 261.98 pg/mL; p < 0.001). ROC analysis demonstrated moderate diagnostic accuracy (area under the curve [AUC]: 0.768, 95% CI: 0.651-0.885; optimal cutoff: 676.13 pg/mL; sensitivity: 66.7%; specificity: 83.7%). Standard inflammatory markers showed no significant differences between groups. Conclusions Reduced ISM1 levels in IGM patients suggest potential involvement in disease pathogenesis. While serum ISM1 shows promise as a supportive biomarker, larger studies, including other inflammatory breast conditions, are needed to confirm specificity and clinical utility.
Keywords: biomarker; diagnosis; idiopathic granulomatous mastitis; inflammation; Isthmin-1